Effect of thrombocytopenia on mode of analgesia/anesthesia and maternal and neonatal outcomes. (April 2014) - Dikman, Daniel; Elstein, Deborah; Levi, Gal Schtrechman; Granovsky-Grisaru, Sorina; Samueloff, Arnon; Gozal, Yaacov; Ioscovich, Alexander
Abstract Objectives: The purpose was to correlate the use of regional analgesia/anasthesia among women with different degrees of thrombocytopenia relative to women with normal platelet counts, and note maternal and neonatal outcome, and mode of delivery. Methods: A case-control paradigm was developed based on women who delivered during 2007–2011 with platelet counts ≤80 000/mm3. For each woman in this "severe" thrombocytopenic group, an age- and parity-matched control was found who delivered a singleton within the same year but whose platelets were either 81 000–150 000/mm3 ("moderate" thrombocytopenia) or ≥151 000/mm3 (normal platelet counts). Results: 168 women were identified for each group; mean maternal age (28.4 years), mean gravidity (4.3), mean parity (3.7), mean gestational age (39.2 weeks) and mean birth weight (3283 g) were comparable. However, only in the severe thrombocytopenic women were there very early preterm deliveries, lowest birth weight, lowest Apgar scores, the greatest number with serious post-partum hemorrhage (>500 ml); use of regional analgesia/anesthesia was lowest, and percent cesarean sections highest. Conclusions: This study highlights potential for adverse maternal outcome of post-partum hemorrhage and adverse neonatal outcomes of prematurity, low birth weight, and low Apgar scores (but not neonatal death), and limited regional analgesia/anesthesia in women who present at delivery with severe (≤80 000/mm3) thrombocytopenia.